2008
DOI: 10.1007/s11243-008-9149-9
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the magnetic exchange behavior of a hetero-double-bridged binuclear copper(II) complex: orbital complementary effect

Abstract: The mechanism of magnetic exchange interaction in a l-chloro and l-methoxy double-bridged copper(II) complex is investigated by calculations based on density functional theory combined with the broken-symmetry approach (DFT-BS). The calculated results reveal that the complex has a strong antiferromagnetic interaction. By the analyses of magnetic orbital interaction and spin distribution, it is found that there exists orbital complementary effect between the two bridging ligands. In addition, to examine the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Polynuclear complexes with bridging groups are currently attracting much attention for their interesting molecular topologies and crystal packing motifs, as well as the fact that they may be designed with specific functionalities [1][2][3]. The rational design and synthesis of polynuclear complexes, aiming at understanding the factors that govern the final structures, are of continuing interest in coordination and structural chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polynuclear complexes with bridging groups are currently attracting much attention for their interesting molecular topologies and crystal packing motifs, as well as the fact that they may be designed with specific functionalities [1][2][3]. The rational design and synthesis of polynuclear complexes, aiming at understanding the factors that govern the final structures, are of continuing interest in coordination and structural chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…(3) was prepared by a similar procedure to that described for (1), with HL 1 replaced by HL3 (0.285 g, 1.0 mmol). Yield: 61%.…”
mentioning
confidence: 99%
“…Obviously, in this binuclear structure the effect of the spin delocalization results in antiferromagnetic interaction. [ 67 ]…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, in this binuclear structure the effect of the spin delocalization results in antiferromagnetic interaction. [67] It is also of interest to estimate the possibility of a SCO phenomenon in the [Fe(tdas) 2 ] 2 2dimer. Since the "reentrant" behavior in magnetic properties of (nBu 4 N)[Fe(tdas) 2 ] salt was detected by K. Awaga et al, [24] MPWLYP1M functional was used for this estimation because it demonstrated good accuracy in reproducing the experimental data of exchange coupling constants in (nBu 4 N)[Fe(tdas) 2 ]: J 2 /k B (exp)=-118 K, [24] J 2 (calc)= -118.2 K (Noodleman's approach, Table 4).…”
Section: Eurjicmentioning
confidence: 99%
“…This technique has been used successfully to explain the coupling mechanism and magneto-structural correlation for the dinuclear transition metal complexes. [34][35][36] In these two dynamic models, the Mn-(m-OCH 3 )-Mn angles are changed from 119 • to 91 • by a step of 4 • with the m 2 -X ligands being pulled away from the Mn(III) centers.…”
Section: Modeling Strategymentioning
confidence: 99%